2019
DOI: 10.3390/v11060548
|View full text |Cite
|
Sign up to set email alerts
|

IFITM3 Clusters on Virus Containing Endosomes and Lysosomes Early in the Influenza A Infection of Human Airway Epithelial Cells

Abstract: Interferon-induced transmembrane proteins (IFITMs) have been shown to strongly affect influenza A virus (IAV) infectivity in tissue culture. Moreover, polymorphisms in IFITM3 have been associated with the severity of the disease in humans. IFITM3 appears to act early in the infection, but its mechanism of action and potential interactions with incoming IAV structures are not yet defined. Here, we visualized endogenous IFITM3 interactions with IAV in the human lung epithelial cell line A549 and in primary human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 78 publications
1
30
1
Order By: Relevance
“…A highly conserved, short amphipathic helix within a hydrophobic region of IFITM3 plays a critical role in IFITM3dependent inhibition of IAV, Zika virus, VSV, EBOV, HIV, and SARS-CoV-2 infections (43,71). IFITM3 may accumulate and locate in endosomal vesicles during IAV infection and eventually coat the IAV-containing endosomal vesicles (76). Moreover, IFITM3 can fuse with the incoming virus and enhance the trafficking of the IFITM-virus cargo to the lysosomes for degradation via specific S-palmitoylation (76,77).…”
Section: Possible Antiviral Mechanism Of Ifitmsmentioning
confidence: 99%
See 1 more Smart Citation
“…A highly conserved, short amphipathic helix within a hydrophobic region of IFITM3 plays a critical role in IFITM3dependent inhibition of IAV, Zika virus, VSV, EBOV, HIV, and SARS-CoV-2 infections (43,71). IFITM3 may accumulate and locate in endosomal vesicles during IAV infection and eventually coat the IAV-containing endosomal vesicles (76). Moreover, IFITM3 can fuse with the incoming virus and enhance the trafficking of the IFITM-virus cargo to the lysosomes for degradation via specific S-palmitoylation (76,77).…”
Section: Possible Antiviral Mechanism Of Ifitmsmentioning
confidence: 99%
“…IFITM3 may accumulate and locate in endosomal vesicles during IAV infection and eventually coat the IAV-containing endosomal vesicles (76). Moreover, IFITM3 can fuse with the incoming virus and enhance the trafficking of the IFITM-virus cargo to the lysosomes for degradation via specific S-palmitoylation (76,77).…”
Section: Possible Antiviral Mechanism Of Ifitmsmentioning
confidence: 99%
“…It was previously reported that IFITM3 forms clusters on virus-containing vesicles ( Kummer et al, 2019 ) and that IFITM3 oligomerization promotes restriction of IAV ( John et al, 2013 ). However, the determinants initially purported to mediate oligomerization (phenylalanines at residues 75 and 78 of the CD225 domain [ John et al, 2013 ]) were later shown to be unnecessary when oligomerization was measured using a FRET-based approach in living cells ( Winkler et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral restriction factor IFITM3 acts as part of innate immune response initial steps to limit influenza infection. It halts the formation of viral membrane fusion pores with host endosomes, by clustering in the IAV containing endosomes, impairing entry into the cytosol and subsequent viral replication (Kummer et al, 2019 ; Suddala et al, 2019 ). In addition, IFITM3 has also been shown to be induced, in DCs, after influenza infection, in mice, and is involved in migration of these cells to lymph nodes and consequent activation of influenza-specific lymphocytes (Infusini et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%